2023
DOI: 10.1002/pbc.30365
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine/irinotecan/temsirolimus upfront window treatment of high‐risk hepatoblastoma: A report from the Children's Oncology Group AHEP0731 Study Committee

Abstract: Background Survival for children with metastatic hepatoblastoma (HB) remains suboptimal. We report the response rate and outcome of two courses of vincristine/irinotecan/temsirolimus (VIT) in children with high‐risk (HR)/metastatic HB. Procedures Patients with newly diagnosed HB received HR window chemotherapy if they had metastatic disease or a serum alpha‐fetoprotein (AFP) level less than 100 ng/mL. Patients received vincristine (days 1 and 8), irinotecan (days 1–5), and temsirolimus (days 1 and 8). Cycles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…While not powered to study outcomes, results from this stratum demonstrated that VI is an effective anti‐tumor combination for patients with advanced disease 18 . Addition of temsirolimus to the VI window (VIT) did not further improve response rates 30 . It is recognized now, in hindsight, that tumors associated with a low AFP level at diagnosis were likely rhabdoid tumors as “low AFP‐secreting HB tumors” are exceedingly rare in current HB trials and often reflective of small tumor size 31 .…”
Section: Recent Findingsmentioning
confidence: 86%
See 1 more Smart Citation
“…While not powered to study outcomes, results from this stratum demonstrated that VI is an effective anti‐tumor combination for patients with advanced disease 18 . Addition of temsirolimus to the VI window (VIT) did not further improve response rates 30 . It is recognized now, in hindsight, that tumors associated with a low AFP level at diagnosis were likely rhabdoid tumors as “low AFP‐secreting HB tumors” are exceedingly rare in current HB trials and often reflective of small tumor size 31 .…”
Section: Recent Findingsmentioning
confidence: 86%
“…18 Addition of temsirolimus to the VI window (VIT) did not further improve response rates. 30 It is recognized now, in hindsight, that tumors associated with a low AFP level at diagnosis were likely rhabdoid tumors as "low AFP-secreting HB tumors" are exceedingly rare in current HB trials and often reflective of small tumor size. 31 Patients with small cell undifferentiated (SCU) histologic features, of any proportion, were restricted to stratum 3 if fully resected, given that this histologic feature was felt to confer a poor prognosis.…”
Section: Systemic Therapymentioning
confidence: 99%